2017
DOI: 10.1177/2151458516685826
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postoperative Outcomes in Elderly Patients With a Do-Not-Resuscitate Order Undergoing Elective and Nonelective Hip Surgery

Abstract: Purpose:Emergency hip surgery generally has worse outcomes than elective hip surgery, even when adjusted for patient and surgical factors. Do-not-resuscitate (DNR) status patients are typically at higher perioperative risk and undergo a narrow range of surgical procedures. We aimed to compare the outcomes after hip surgery of differing degrees of urgency in this cohort.Materials and Methods:Using National Surgical Quality Improvement Program (NSQIP) data, we conducted univariate and multivariate analyses compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
0
14
3
Order By: Relevance
“…The most common procedures among DNR patients focused on symptom relief but were also associated with higher rates of 30 d mortality (but not morbidity) when compared to non-DNR matched controls[ 8 ]. In another analysis focused on DNR patients undergoing hip surgery, the urgency of the procedure (emergent vs non-emergent) was found to cause no independent increase in 30-d morbidity, while DNR status itself again demonstrated high 30-d mortality rates in excess of those predicted by the NSQIP risk calculator[ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common procedures among DNR patients focused on symptom relief but were also associated with higher rates of 30 d mortality (but not morbidity) when compared to non-DNR matched controls[ 8 ]. In another analysis focused on DNR patients undergoing hip surgery, the urgency of the procedure (emergent vs non-emergent) was found to cause no independent increase in 30-d morbidity, while DNR status itself again demonstrated high 30-d mortality rates in excess of those predicted by the NSQIP risk calculator[ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some clinicians also worry that by recording a DNAR decision, this may compromise other aspects of the patient's care. This is not unreasonable as systematic reviews have shown that surgical patients with DNARs have a worse mortality even when adjusted for other risk factors [12][13][14]. However, analysis has shown that in the hip fracture subgroup, DNAR is not an independent mortality risk factor [15].…”
Section: Discussionmentioning
confidence: 99%
“…To take a similar example, past literature has demonstrated a strong association between do-not-resuscitate (DNR) status and adverse outcomes. [20][21][22][23][24] In all likelihood, the DNR status does not directly cause worse outcomes so much as it marks a sick and vulnerable population. Selection bias at the individual patient level may contribute to an association between comanagement and worse outcomes.…”
Section: Discussionmentioning
confidence: 99%